Ocular hemodynamics in patients with stage I-IV keratoconus - Ivanovskaia, E.V.; Khramenko, N.I.; Drozhzhyna, G.I. (Ukrainian Journal of Ophthalmology, 2026)
Background. Keratoconus is a progressive dystrophic condition of the cornea. Dystrophic changes in keratoconus are observed in the connective tissues of the sclera, drainage area, and iris. The role of a vascular factor in the development of such diseases as glaucoma, uveitis, and cataract is well-known. In this respect, studying the ocular blood supply in keratoconus appears to be reasonable. Material and Methods. Rheography was performed in 90 patients (125 eyes), aged 16-39, with keratoconus of stages I-V and the volume pulse blood flow in the eye was determined according to rheographic coefficient (RQ (‰)). In 21 eyes, stage IV-V keratoconus was accompanied by ocular hypertension and non-penetrating deep sclerotomy was performed. Depending on volume pulse blood flow rates and a vascular tone in the eye, 14 patients (28 eyes) with stage I-V keratoconus were treated using anti-ischemic and antioxidant drugs. Results. The decreased blood flow rates were noted in the eyes in each group as compared to norm. Volume blood flow was decreased by 26.7% in the eyes of the patients with stage II, III, and IV and by 44.8% in stage V keratoconus as compared to healthy patients of the same age. Volume blood flow RQ was 2.36±0.40 ‰ in stage IV-V keratoconus, complicated by ocular hypertension above 27 mmHg, i.e. by 43.8% lower than the age norm. Volume blood flow in the patients with stage IV keratoconus and intraocular hypertension was by 22.3% lower as compared with the uncomplicated course of stage IV keratoconus. Non-penetrating deep sclerotomy (NPDS) for ocular hypertension in the patients with stage IV-V keratoconus facilitated an increase in volume blood flow by 72.5%; RQ increased from 2.36±0.4 ‰ to 4.07±0.7 ‰), р <0.05. The vascular tone increased in large vessels in 41.6-82.3% of cases in all disease stages and in small vessels in 21.4-33.3% of cases in initial stages and in 50-71.4%% in III-V stages. The treatment resulted in significantly increased volume blood flow in the eye: RQ increased from initial 2.56±0.23 ‰ to 3.20±0.26 ‰, i.e by 25% (р = 0.006). Conclusions. 1. Volume pulse blood flow in the eyes of the keratoconus patients was significantly decreased as compared to the age norm: by 26.6% and by 44.7% in patients with keratoconus of stages II-IV and of stage V, respectively. 2. When keratoconus was complicated by intraocular hypertension, the decrease in volume pulse blood flow was more expressed: that was by 22.6 % lower in stage IV patients than in those with eutonia and by 44% lower than the age norm. 3. Surgery (NPDS) in patients with stage IV-V keratoconus, complicated by intraocular hypertension, facilitated the improvement of visual functions, normalization not only of intraocular pressure but also of ocular blood circulation, which was evidenced by the increase of volume pulse blood flow by 72.5%. 4. The comprehensive drug treatment including anti-ischemic and antioxidant medications resulted in improved ocular hemodynamics in volume pulse blood flow by 25%, stabilized visual functions and subjectively better visual performance.